El sector informal y su influencia en la actividad comercial del cantón Mocache, periodo 2010-2014. - Mendoza Aguilera, Estefania Adelaida (2015)
The present research on "The informal sector and its influence on the business of Mocache canton period 2010-2014". It has as main objective, to identify socio-economic characteristics of the informal-sector and their impact on business, plus unemployment as a factor in the increase and possible causes that generate informal trade in the central streets of the city. The theoretical foundation addresses the following semantic categories: Economic development, formal sector, trade, informal trade, unemployment, factors which cause informality, informal economy, and its legal basis. The results of the research factual basis of the respective surveys of informal traders, interviews with Ms. President of the Alliance and Progress Association, through direct observation by the commercial activities of the central streets of the city, managed to get the information necessary for verification of the hypothesis, namely: "The informal sector, as estimable impact on the commercial activity of the canton Mocache, period 2010-2014". The same is checked according to what they declare informal traders. Among the results, we cite the most significant: In relation to the informal sector surveys of downtown Canton Mocache, we determined that 100% of informal traders would agree that the authorities of the Autonomous Decentralized Government (GAD) implement programs and strategies to help the informal trade….